Phylogeny of anion exchangers: Could trout AE1 conductive properties be shared by other members of the gene family? - Guizouarn, Hélène; Christen, Richard; Borgese, Franck (Biochimica et biophysica acta, 2005)
A phylogenetic tree of anion exchangers (AE) was performed in order to better understand relationships between the different known AE and how they arose. Indeed, the different known AE1 from mammals or fish do not exhibit the same transport features: all studied anion exchangers 1 (AE1) catalyse an electroneutral Cl −/HCO 3 − exchange through the plasma membrane; however, trout AE1 (tAE1) is able to spontaneously form an anion conductive pathway permeable to some inorganic cations (Na + and K +) as well as to organic osmolytes such as taurine. Therefore, it has been proposed that this major erythrocyte membrane protein could play a key role for the cell volume regulation of trout red cells. By analogy, it was envisioned that other fish anion exchangers could play a similar role in osmolyte loss induced by erythrocyte swelling. We have cloned AE1 from Raja erinacea and Danio rerio and studied their properties after expression in Xenopus laevis oocytes. In this study, we show that none of them is able to induce any conductive pathway or taurine permeability in Xenopus oocytes. Our phylogenetic analyses show that, first, all present AE1 genes have a common ancestor distinct from that of AE2 and AE3 and second, tAE1 is a true AE1 ortholog. The question of whether tAE1 conductive properties are a derived character in the trout lineage within Euteleostei or whether other AE1 members can share these properties is then discussed.